The penta-X syndrome. Issue 5 (October 1980) - Monheit, A; Francke, U; Saunders, B; Jones, K L
Abstract : A child is presented with a 49, XXXXX chromosomal constitution bringing to 12 the total number of children described with this karyotype. Comparison of this child's features with previously reported cases indicates a clinically recognisable specific pattern of malformations referred to as the penta-X syndrome. X chromosome replication studies using BrdU labelling in the patient's cells clearly showed that the four presumably inactive X chromosomes were late replicating but not in a strictly synchronous fashion.